Enhancing Student Ecoliteracy through an ESD-Inquiry Website on Mangrove Biodiversity - Firmansyah, Fahmie; Rosadi, Edi (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to develop an inquiry-based Education for Sustainable Development (ESD) oriented website that focuses on mangrove in the Pulau Dua Nature Reserve to enhance high school students’ ecoliteracy. The research addresses the limited availability of digital learning media that successfully integrate local environmental content with inquiry-driven learning approaches. Method: The study applied the ADDIE model, which includes analysis, design, development, implementation, and evaluation phases. Validation was conducted by media and material experts, followed by classroom implementation with selected high school students in Serang Regency. Data collection combined quantitative and qualitative methods. Quantitative data were obtained from pretest and posttest assessments on ecoliteracy indicators, while qualitative data were gathered through expert reviews and teacher interviews. Results: The results indicated a significant improvement in students' ecoliteracy, covering cognitive, affective, and behavioral dimensions. All six measured aspects showed positive development, including ecological knowledge, environmental awareness, attitudes and values, ecological skills, critical and reflective thinking, and environmental action. The effectiveness was confirmed through statistical analysis using paired sample t-tests. Novelty: The novelty of this research lies in the integration of local environmental issues into a digital learning platform that promotes critical thinking and sustainability-oriented behavior. The website provides a contextual and interactive learning experience that connects ecological content with global sustainability perspectives. These findings demonstrate the potential of localized and inquiry-based digital tools to strengthen students' understanding and commitment to sustainable development.